1985
DOI: 10.1161/01.hyp.7.6_pt_2.ii157
|View full text |Cite
|
Sign up to set email alerts
|

Indapamide in the treatment of hypertension in non-insulin-dependent diabetes.

Abstract: I T is well recognized that hypertensive patients with diabetes have more than double the frequency of heart disease seen in normotensive diabetic patients' and that blood pressure control over long periods of time delays or prevents many vascular complications. 2 In hypertensive nondiabetic patients the reduction of diastolic pressure under 90 mm Hg reduces morbidity and mortality, 3 and there is evidence that the same holds true for hypertensive diabetic persons. It has been shown that early and aggressive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
0
12
1
1
Order By: Relevance
“…In the Abbou study, 15 indapamide was administered for 4 months, and a significant reduction in blood pressure was observed after 6 weeks of treatment. In another study, 22 performed in diabetic patients, an evident antihypertensive effect was present after only 4 weeks of therapy. In our study, the D+I combination was able to normalise blood pressure in more than 70% of the patients after 1 month, and in more than 90% after 2 months of treatment.…”
Section: Discussionmentioning
confidence: 92%
“…In the Abbou study, 15 indapamide was administered for 4 months, and a significant reduction in blood pressure was observed after 6 weeks of treatment. In another study, 22 performed in diabetic patients, an evident antihypertensive effect was present after only 4 weeks of therapy. In our study, the D+I combination was able to normalise blood pressure in more than 70% of the patients after 1 month, and in more than 90% after 2 months of treatment.…”
Section: Discussionmentioning
confidence: 92%
“…The non-thiazide diuretic indapamide fulfills the overall criteria for a diuretic to be used in combination with other antihypertensive agents since it effectively lowers the blood pressure and does not compromise serum cholesterol 14 or plasma glucose levels 15 while it also reduces left ventricular hypertrophy (LVH). 16 The formulation of perindopril and idapamide has been shown to provide multiple ancillary benefits in an experimental model of salt-sensitive hypertension.…”
Section: The Importance Of a Diuretic Componentmentioning
confidence: 99%
“…Indapamide in a dose of 2.5 mg/day has been shown to be effective in the treatment of moderate hypertension in patients with normal renal function [7], in those with renal failure [1], in elderly patients [8][9][10] and in those with diabetes mellitus [4,5,11].…”
Section: Discussionmentioning
confidence: 99%
“…There were only small decrements in the serum levels of potassium and a small increment in plasma uric acid concentration. Apart from a few cases where blood glucose levels have risen following indapamide therapy, the overall results of studies of up to 1 year's duration have shown that 2.5 mg indapamide/day does not adversely affect glucose tolerance in diabetic and nondiabetic hypertensive patients [4,5,11,14]. Similarly, this dose of indapamide did not cause a significant increment in total plasma cholesterol, triglycerides or low density and high density lipoproteins [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation